The Association of Sports Participation With Depressive Symptoms and Anxiety Disorder in Adolescents - Chi, Guijun; Wang, Lei (Frontiers in Public Health, 2022)
Aim: A growing body of evidence has indicated that physical activity is negatively associated with depression and anxiety in adolescents, while the associations between different modalities of PA with depression and anxiety have yet been explored well. This study aimed to explore the association between sport participation and depression and anxiety in adolescents of a Chinese sample. Methods: 2374 adolescents from 8 schools were invited to take part in this survey, of whom 1714 adolescents of 7, 8, 10 and 11 grades were included for final analysis. Depressive symptom and anxiety disorder was assessed by the Patient Health Questionnaire – 9 (PHQ-9) and the Generalised Anxiety Disorder – 7 (GAD-7), respectively. Sport participation was assessed using one single question. Sociodemographic factors were also assessed by a self-reported questionnaire. Ordinal logistic regression was used to estimate the associations of sport participation with depressive symptoms and anxiety disorders, separately, after controlling for all the sociodemographic covariates. Results: Of all the study participants, those with fewer participations in sport-related activities were more likely to report depressive symptoms (Odd ratio [OR] for never = 2.07; OR for 1-3 times per month = 1.77; OR for 1-2 times per week = 1.77).) and anxiety disorders (OR for never = 1.61; OR for 1-3 times per month = 1.69; OR for 1-2 times per week = 1.38). Conclusion: Encouraging adolescents engage in more sport participations would be an effective and feasible approach for mental health promotion. Future China-based studies are encouraged to replicate or negate our study findings.